Operability of educational services funds in the Capital District (2018)
Educational Services Funds are accounting accounts of educational establishments, created as a budgetary management mechanism and execution of resources for the proper administration of their income and to meet their operating and investment expenses other than personnel Through the analysis of the information collected, the assessment of the budgetary execution of the funds in the Capital District will be carried out with the transfer information of the year 2017, made by the Ministry of Education, the Secretary of Education of Bogotá and the budget execution. of 30 Education Service funds from different localities of the city, issuing statistical information and the analysis of figures that would generate the issuance of conclusions regarding the execution based on its regulatory framework, Law 715 and its regulatory decree 4791.